2013
DOI: 10.4102/pythagoras.v34i2.198
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a group approach on the performance of high school mathematics learners

Abstract: In this study, we investigated the effects of a group approach versus a non-group approach on the mathematics performance of learners. A group approach refers to an arrangement in which learners sit together to discuss and solve mathematics tasks. We studied a convenience sample of low-performing Grade 10 mathematics learners using a quasi-experimental design with a non-equivalent control group. The experimental group was taught using a group approach and the control group using non-group approach instruction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Studies have shown that instructional strategy has influence on learning outcomes (Fatade, Arigbabu, Mogari, & Awofala, 2014;Awofala, Fatade, & Ola-Oluwa, 2012;Awofala & Nneji, 2012;Awofala, 2011a;Awofala, 2011b;Dhlamini & Mogari, 2013), attitudes affect cognition (Zan & Di Martino, 2007;Elenchothy, 2007) and mathematics word problem (Bate & Wiest, 2004) is often perceived a difficult topic in senior secondary school mathematics (Akinsola & Awofala, 2009). Because mathematics teachers are among the most important factors in student learning of mathematics, they have the onerous task of implementing effective instructional strategy capable of positively influencing students' attitudes toward mathematics word problem.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that instructional strategy has influence on learning outcomes (Fatade, Arigbabu, Mogari, & Awofala, 2014;Awofala, Fatade, & Ola-Oluwa, 2012;Awofala & Nneji, 2012;Awofala, 2011a;Awofala, 2011b;Dhlamini & Mogari, 2013), attitudes affect cognition (Zan & Di Martino, 2007;Elenchothy, 2007) and mathematics word problem (Bate & Wiest, 2004) is often perceived a difficult topic in senior secondary school mathematics (Akinsola & Awofala, 2009). Because mathematics teachers are among the most important factors in student learning of mathematics, they have the onerous task of implementing effective instructional strategy capable of positively influencing students' attitudes toward mathematics word problem.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of Figure 1, more of the WM resources could be availed when the extraneous load is reduced. In the current study this is achieved by presenting learning materials grounded in learners' every day's experience (see, Dhlamini & Mogari, 2013). According to CLT, learning that takes place in familiar settings reduces the effects of cognitive load or the extraneous load.…”
Section: Germane Cognitive Loadmentioning
confidence: 99%
“…The choice of the topics was motivated by their perceived challenging nature to Grade 10 mathematics learners. When teachers were asked about topics that gave learners problems topics in Financial Mathematics were prominently listed (Dhlamini & Mogari, 2013). Learners' socioeconomic background, which was a township in this case, presented a context to generate effective instructional conditions for the study.…”
Section: The Pilot Studymentioning
confidence: 99%
See 1 more Smart Citation